Mental and physical health characteristics of older and younger adults receiving medication for opioid use disorder - Walker, Teresa J.; Mohankumar, Rakshitha; Kraus, Shane W.; Cotton, Brandi P.; Renn, Brenna N. (Frontiers in Public Health, 2024)
Background: Methadone is an effective and widely used medication for opioid use disorder (MOUD). Within in the United States (US), older adults represent an increasing proportion of those receiving MOUD, yet little is known about their characteristics. Objectives: To evaluate mental and physical health characteristics of younger and older adults receiving MOUD and test whether age moderates the relation between physical and mental health variables. Methods: Data for this secondary analysis are drawn from a cross-sectional survey of a convenience sample of individuals seeking methadone dosing as part of MOUD at four opioid treatment programs in two regions of the US. Descriptive statistics and correlational and moderation analyses examined outcomes of pain severity, pain interference, self-rated health, physical activity, depression, and anxiety across younger (18-49) and older (50+ years) participants. Results: Analyses included 469 participants (mean [range] age, 41.01 [20-70] years). Older participants reported higher pain severity and interference, less physical activity, and worse self-rated health than those in the younger age group. Associations between mental and physical health variables were generally weak-to-moderate in the older age group and weak in the younger age group. Age did not moderate associations. Clinically significant mental and physical health variables are associated among individuals receiving methadone for MOUD, with older adults facing unique challenges. Conclusions: Opioid use treatment should include pain management, assessment and treatment of depression and anxiety, and optimization of health behaviors (e.g., physical activity) across age groups. Pain management and health promotion are relevant targets for aging individuals receiving MOUD.